PENGARUHÃÂ INFORMASIÃÂ KEWIRASWASTAANÃÂ ÃÂ TERHADAPÃÂ MINATÃÂ MAHASISWAÃÂ UNTUKÃÂ BERWIRASWASTAÃÂ ÃÂ - MuslihÃƒÂ‚Ã‚Â , Muhamad; KhumaediÃƒÂ‚Ã‚Â ÃƒÂ‚Ã‚Â , M.ÃƒÂ‚Ã‚Â ; AlÃƒÂ‚Ã‚Â JananÃƒÂ‚Ã‚Â , Dony HidayatÃƒÂ‚Ã‚Â (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Negeri Semarang, 2008)
TujuanÃÂ penelitianÃÂ iniÃÂ adalahÃÂ untukÃÂ mengetahuiÃÂ tingkatÃÂ informasiÃÂ kewiraswastaan,ÃÂ mengukurÃÂ minatÃÂ mahasiswaÃÂ dalamÃÂ berwiraswasta,ÃÂ mengujiÃÂ pengaruhÃÂ informasiÃÂ kewiraswastaanÃÂ terhadapÃÂ minatÃÂ berwiraswasta,ÃÂ sertaÃÂ mengetahuiÃÂ pengaruhÃÂ informasiÃÂ kewiraswastaanÃÂ terhadapÃÂ minatÃÂ berwiraswastaÃÂ padaÃÂ mahasiswaÃÂ PendidikanÃÂ TeknikÃÂ Mesin,ÃÂ FakultasÃÂ Teknik,ÃÂ UniversitasÃÂ NegeriÃÂ SemarangÃÂ angkatanÃÂ 2006.ÃÂ PenelitianÃÂ iniÃÂ mengunakanÃÂ metodeÃÂ survai,ÃÂ denganÃÂ populasiÃÂ 80ÃÂ orangÃÂ mahasiswa.ÃÂ HasilÃÂ analisisÃÂ deskriptifÃÂ menunjukkanÃÂ bahwaÃÂ minatÃÂ mahasiswaÃÂ untukÃÂ berwiraswastaÃÂ tergolongÃÂ baik.ÃÂ TingkatÃÂ informasiÃÂ kewiraswastaanÃÂ yangÃÂ diterimaÃÂ mahasiswaÃÂ jugaÃÂ tergolongÃÂ baik.ÃÂ HasilÃÂ analisisÃÂ regresiÃÂ menunjukkanÃÂ besarnyaÃÂ pengaruhÃÂ informasiÃÂ kewiraswastaanÃÂ terhadapÃÂ minatÃÂ berwiraswastaÃÂ sebesarÃÂ 49,28%.ÃÂ HendaknyaÃÂ semuaÃÂ pihakÃÂ dapatÃÂ memberikanÃÂ informasiÃÂ kewiraswastaanÃÂ kepadaÃÂ mahasiswaÃÂ danÃÂ mahasiswaÃÂ jugaÃÂ aktifÃÂ mencariÃÂ informasiÃÂ tersebutÃÂ sehinggaÃÂ dapatÃÂ menumbuhkanÃÂ jiwaÃÂ entrepreneurshipÃÂ padaÃÂ diriÃÂ setiapÃÂ mahasiswa. ÃÂ KataÃÂ kunci:ÃÂ informasiÃÂ kewiraswastaan,ÃÂ minatÃÂ berwiraswastaTheÃÂ objectivesÃÂ ofÃÂ thisÃÂ researchÃÂ areÃÂ toÃÂ knowÃÂ theÃÂ entrepreneurialÃÂ informationÃÂ level,ÃÂ toÃÂ measureÃÂ studentsÃ¢â¬â¢ÃÂ interestÃÂ inÃÂ beingÃÂ entrepreneurs,ÃÂ toÃÂ testÃÂ theÃÂ effectÃÂ ofÃÂ entrepreneurialÃÂ informationÃÂ towardÃÂ studentsÃ¢â¬â¢ÃÂ interestÃÂ toÃÂ beÃÂ entrepreneurs,ÃÂ andÃÂ toÃÂ identifyÃÂ theÃÂ effectÃÂ ofÃÂ entrepreneurialÃÂ informationÃÂ towardÃÂ studentsÃÂ atÃÂ echanicalÃÂ EngineeringÃÂ EducationÃÂ FacultyÃÂ ofÃÂ EngineeringÃÂ SemarangÃÂ StateÃÂ UniversityÃÂ yearÃÂ 2006.ÃÂ ThisÃÂ researchÃÂ usedÃÂ surveyÃÂ methodÃÂ withÃÂ populationÃÂ consistingÃÂ ofÃÂ 80ÃÂ students.ÃÂ TheÃÂ descriptiveÃÂ resultÃÂ showsÃÂ thatÃÂ studentsÃ¢â¬â¢interestÃÂ toÃÂ beÃÂ entrepreneursÃÂ isÃÂ inÃÂ goodÃÂ quality.ÃÂ TheÃÂ regressiveÃÂ analysisÃÂ resultÃÂ showsÃÂ thatÃÂ theÃÂ percentageÃÂ ofÃÂ entrepreneurialÃÂ informationÃÂ effectÃÂ towardÃÂ studentsÃ¢â¬â¢ÃÂ interestÃÂ inÃÂ beingÃÂ entrepreneursÃÂ isÃÂ 49,28%.ÃÂ ItÃÂ isÃÂ suggestedÃÂ thatÃÂ allÃÂ peopleÃÂ couldÃÂ explainÃÂ entrepreneurialÃÂ informationÃÂ toÃÂ students.ÃÂ InÃÂ turn,ÃÂ theÃÂ studentsÃÂ themselvesÃÂ shouldÃÂ beÃÂ activeÃÂ inÃÂ graspingÃÂ theÃÂ informationÃÂ soÃÂ theirÃÂ motivationÃÂ andÃÂ spiritÃÂ toÃÂ beÃÂ entrepreneursÃÂ willÃÂ grow. Keywords:ÃÂ entrepreneurialÃÂ information,ÃÂ interestÃÂ inÃÂ beingÃÂ entrepreneurs ÃÂ ÃÂ